Negative electrode agent for non-aqueous electrolyte secondary battery, negative electrode for non-aqueous electrolyte secondary battery, and non-aqueous electrolyte secondary battery

The use of a mixed binder system with crosslinked polyacrylate and copolymerized polyacrylic acid ester/polyacrylic acid, along with silicon and carbon-based active materials, in the negative electrode agent of nonaqueous electrolyte secondary batteries addresses the challenges of volume change and cycle degradation, thereby improving energy density.

JP7661677B2Active Publication Date: 2025-04-15TOPPAN HOLDINGS INC
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2020086870
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-05-18
Publication Date
2025-04-15
Estimated Expiration
2040-05-18

AI Technical Summary

Technical Problem

Existing negative electrodes for nonaqueous electrolyte secondary batteries, particularly those using silicon-based active materials, face challenges in maintaining energy density due to large volume changes during charge and discharge, leading to disconnection, peeling, and deterioration in cycle characteristics.

Method used

A negative electrode agent comprising a mixed binder with a first polymer crosslinked with a polyacrylate salt and a second polymer copolymer of polyacrylic acid ester and polyacrylic acid, combined with a silicon-based and a carbon-based active material, which improves the mechanical strength and cycling characteristics while maintaining energy density.

Benefits of technology

The proposed solution enhances the energy density of nonaqueous electrolyte secondary batteries by improving the mechanical strength and cycle characteristics of the negative electrode, effectively addressing the issues of volume change and active material isolation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007661677000002
    Figure 0007661677000002
  • Figure 0007661677000003
    Figure 0007661677000003
  • Figure 0007661677000001
    Figure 0007661677000001
Patent Text Reader

Abstract

To provide a negative electrode agent for a nonaqueous electrolyte secondary battery, a negative electrode for a nonaqueous electrolyte secondary battery, and a nonaqueous electrolyte secondary battery that are capable of improving energy density.SOLUTION: A negative electrode agent for a nonaqueous electrolyte secondary battery includes an electrode active material, a conductive assistant 13, and a binder 14. The binder 14 is a mixed binder including a first high polymer whose average molecular weight is within a range of 500,000 or more and 5,000,000 or less, and a second high polymer whose average molecular weight is within a range of 5,000 or more and 50,000 or less. The electrode active material includes a silicon-based active material 11 and a carbon-based active material 12. The first high polymer has ethylenic unsaturated carboxylic acid salt, and includes a crosslinked structure. The second high polymer is a copolymer of an ethylenic unsaturated carboxylic acid compound and an ethylenic unsaturated compound including an alkylcarboxylic acid ester group.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a negative electrode agent for a nonaqueous electrolyte secondary battery, a negative electrode for a nonaqueous electrolyte secondary battery, and a nonaqueous electrolyte secondary battery, and in particular to a negative electrode agent for a nonaqueous electrolyte secondary battery, a negative electrode for a nonaqueous electrolyte secondary battery, and a nonaqueous electrolyte secondary battery that can improve energy density. [Background technology]

[0002] Non-aqueous electrolyte secondary batteries such as lithium-ion secondary batteries, which have already been widely adopted as power sources for mobile devices such as notebook personal computers and mobile phones, have been attracting attention in recent years in new fields, such as their installation in electric vehicles, etc. In the field of automobiles, the performance required of lithium-ion secondary batteries is particularly important in terms of increasing the energy density of secondary batteries to improve driving range. Generally, negative electrodes made of graphite-based active materials are used as negative electrodes for lithium-ion secondary batteries, but the theoretical capacity of graphite is 372 mAh per gram of active material. In contrast, silicon (Si) and tin (Sn) have been attracting attention in recent years as active materials that have a capacity greater than that of graphite. The theoretical capacity of Si is 4200 mAhg per amount of active material. -1 Similarly, Sn is 990mAhg -1 It is.

[0003] On the other hand, since Si has a capacity about 11 times that of graphite, the volume change accompanying the absorption and release of Li is also large. Specifically, the volume of Si increases by about 4 times due to Li absorption. Compared to graphite, electrodes using active materials with large capacity have a risk of disconnection of the conductive path of the electrode, detachment from the electrode due to pulverization, and peeling of the active material layer from the current collector due to the large volume change accompanying charge and discharge. This may be a factor that reduces the cycle characteristics of secondary batteries. For this reason, development is also being carried out on anodes using metal oxides, which have smaller discharge capacity than the above metals but also have smaller volume expansion, but the same problem has not been completely solved even with metal oxide-based active materials.

[0004] Another factor that reduces cycle characteristics is the consumption of lithium ions accompanying the formation of a solid electrolyte interphase (SEI). In particular, for silicon-based active materials that undergo large volume changes during charging and discharging, the destruction and formation of the SEI can be repeated, so the consumption of lithium ions accompanying the formation of the SEI cannot be ignored. The negative electrode for a lithium-ion secondary battery is usually obtained by mixing a binder, a negative electrode active material, a conductive additive, and a solvent to form a coating liquid (slurry for the negative electrode), which is then coated on a current collector and dried to form a negative electrode agent layer.

[0005] The present inventors have focused on the function of the binder in the negative electrode for a non-aqueous electrolyte secondary battery as a target for solving the above problems and have conducted research. An invention has been disclosed that suppresses the decrease in capacity due to repeated charging and discharging by bonding a substance containing a repeating unit of alkylene oxide to the surface of a metal active material, which is a negative electrode active material made of metal particles that can be alloyed with lithium, to form a material layer (Patent Document 1). Although the elasticity of this material layer can partially absorb the expansion of the active material, if the expansion and contraction of the active material is large, the volume change cannot be absorbed and sufficient cycle characteristics cannot be obtained.

[0006] It has also been disclosed that cross-linked polyacrylic acid is used as a binder (binding agent) when an active material containing a silicon material is used. It is described that this cross-linked polyacrylic acid has superior cycle characteristics compared to non-cross-linked polyacrylic acid. This is because the electrode structure is less likely to be destroyed by the cross-linking (Patent Document 2). Although the use of crosslinked polyacrylic acid as a binder has been shown to improve cycle characteristics, the decrease in discharge capacity retention rate remains a problem.

[0007] In particular, although it is effective in improving the mechanical strength of the coating film, a crosslinked binder is less stretchable than a non-crosslinked binder, and therefore the crosslinked binder covering the surface of the active material cannot keep up with the volumetric changes of the active material, which may result in cracks. As a result, if a large amount of conductive assistant is contained in the negative electrode agent to prevent the active material from becoming isolated and the battery performance from deteriorating even if a crack occurs, the ratio of active material in the negative electrode agent decreases, and therefore there is a risk that the energy density of lithium-ion secondary batteries according to the conventional technology will decrease. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] JP 2007-157709 A [Patent Document 2] International Publication No. 2015 / 163302 Summary of the Invention [Problem to be solved by the invention]

[0009] In view of the above problems, an object of the present invention is to provide a negative electrode agent for a non-aqueous electrolyte secondary battery, a negative electrode for a non-aqueous electrolyte secondary battery, and a non-aqueous electrolyte secondary battery that can improve the energy density. Thus, the present invention relates to a negative electrode agent for a nonaqueous electrolyte secondary battery, a negative electrode for a nonaqueous electrolyte secondary battery, and a nonaqueous electrolyte secondary battery, and in particular to a negative electrode agent for a nonaqueous electrolyte secondary battery, a negative electrode for a nonaqueous electrolyte secondary battery, and a nonaqueous electrolyte secondary battery that can improve energy density. [Means for solving the problem]

[0010] The present invention relates to a negative electrode agent for a non-aqueous electrolyte secondary battery, which contains an electrode active material, a conductive assistant, and a binder, and which contains a first polymer formed by crosslinking a polyacrylate having an average molecular weight in the range of 500,000 to 5,000,000, a second polymer which is a copolymer of a polyacrylate ester and polyacrylic acid having an average molecular weight in the range of 5,000 to 50,000, a silicon-based active material, and a carbon-based active material, thereby improving energy density and solving the above-mentioned problems, and has led to the completion of the present invention.

[0011] A negative electrode agent for a non-aqueous electrolyte secondary battery according to one embodiment of the present invention includes an electrode active material, a conductive assistant, and a binder. The binder is a mixed binder including a first polymer having an average molecular weight in the range of 500,000 to 5,000,000 and a second polymer having an average molecular weight in the range of 5,000 to 50,000. The electrode active material includes a silicon-based active material and a carbon-based active material. The first polymer has an ethylenically unsaturated carboxylate and has a crosslinked structure. The second polymer is a copolymer of an ethylenically unsaturated carboxylic acid compound and an ethylenically unsaturated compound containing an alkyl carboxylate group.

[0012] In the negative electrode agent for a nonaqueous electrolyte secondary battery according to one embodiment of the present invention, the first polymer may be a polymer obtained by crosslinking a polyacrylate having an average molecular weight in the range of 500,000 or more and 5,000,000 or less, and the second polymer may be a copolymer of a polyacrylate ester and polyacrylic acid having an average molecular weight in the range of 5,000 or more and 50,000 or less. In the negative electrode agent for a non-aqueous electrolyte secondary battery according to one embodiment of the present invention, the sum of the surface areas S (m 2 The ratio S / B of the amount of the binder (g) to the mass B of the binder (g) may be in the range of 20 to 400. In the negative electrode agent for a non-aqueous electrolyte secondary battery according to one embodiment of the present invention, the first polymer may be crosslinked with any one of a carbodiimide-based compound, an isocyanate-based crosslinking agent, and an aziridine-based compound.

[0013] In the negative electrode agent for a non-aqueous electrolyte secondary battery according to one aspect of the present invention, the first polymer may be crosslinked with an aziridine compound. In the negative electrode agent for a non-aqueous electrolyte secondary battery according to one aspect of the present invention, the content ratio of the second polymer may be within a range of 1 mass % or more and 20 mass % or less with respect to the total mass of the polymers contained in the mixed binder. A negative electrode for a non-aqueous electrolyte secondary battery according to one aspect of the present invention is characterized in that it is formed using the above-mentioned negative electrode agent for a non-aqueous electrolyte secondary battery. A non-aqueous electrolyte secondary battery according to one aspect of the present invention includes the above-described negative electrode for a non-aqueous electrolyte secondary battery. Effect of the Invention

[0014] According to the present invention, it is possible to provide a negative electrode agent for a non-aqueous electrolyte secondary battery, a negative electrode for a non-aqueous electrolyte secondary battery, and a non-aqueous electrolyte secondary battery that are capable of improving the energy density. [Brief description of the drawings]

[0015] [Figure 1] 1 is a schematic cross-sectional view showing an example of a configuration of a negative electrode for a nonaqueous electrolyte secondary battery according to an embodiment of the present invention. [Diagram 2] FIG. 1 is a schematic cross-sectional view showing the configuration of a known coin cell used for evaluating energy density. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] Hereinafter, a negative electrode for a non-aqueous electrolyte secondary battery according to an embodiment of the present invention and a method for producing the same will be described. Note that the embodiment of the present invention is not limited to the embodiment described below, and modifications such as design changes can be made based on the knowledge of a person skilled in the art, and such modified embodiments can also be included in the scope of the embodiment of the present invention. 1 is a cross-sectional schematic diagram showing an example of the configuration of a negative electrode for a non-aqueous electrolyte secondary battery according to an embodiment of the present invention. The negative electrode for a non-aqueous electrolyte secondary battery 1 according to this embodiment is composed of a negative electrode current collector 21 and a negative electrode active material layer 10 formed on the current collector 21. The negative electrode active material layer 10 is composed of a silicon-based active material 11, a carbon-based active material 12, a conductive assistant 13, and a binder 14.

[0017] Each of the above-mentioned compositions will now be described. <Negative electrode agent for non-aqueous electrolyte secondary batteries> (binder) The binder 14 contained in the negative electrode agent for a non-aqueous electrolyte secondary battery for forming the negative electrode 1 for a non-aqueous electrolyte secondary battery according to this embodiment is a mixed binder containing a first polymer having an ethylenically unsaturated carboxylate and having a crosslinked structure, and a second polymer which is a copolymer of an ethylenically unsaturated carboxylic acid compound and an ethylenically unsaturated compound containing an alkyl carboxylate group. The first polymer has an average molecular weight in the range of 500,000 to 5,000,000, and the second polymer has an average molecular weight in the range of 5,000 to 50,000. The copolymerization ratio of the ethylenically unsaturated carboxylic acid compound and the ethylenically unsaturated compound containing an alkyl carboxylate group in the second polymer, that is, the esterification rate, is preferably in the range of 20% to 90%, more preferably in the range of 50% to 80%. If the esterification rate exceeds 90%, it becomes difficult to form a crosslink with the first polymer, the binding property decreases, and the cycle characteristics decrease. If the esterification rate is less than 20%, the second polymer is easily aggregated, and the cycle characteristics decrease.

[0018] [First Polymer] The first polymer according to this embodiment may be any polymer containing a carboxyl group, and may be, for example, alginic acid, carboxymethylcellulose, hyaluronic acid, rosin acid polymer, polyacrylic acid, a copolymer of maleic acid and acrylic acid, or a salt or ester thereof. The first polymer according to this embodiment may be calcium polyacrylate. Among the above-mentioned substances, polyacrylic acid and its salts or esters, or calcium polyacrylate are particularly preferable. The polymer material used for the binder 14 according to the present embodiment contains many carboxyl groups, which improves the conductivity of lithium ions and suppresses the swelling of the electrolyte, thereby suppressing the reductive decomposition of the electrolyte.

[0019] The first polymer according to this embodiment may have an average molecular weight in the range of 500,000 to 5,000,000. If the average molecular weight is less than 500,000, the binding force is reduced, and a large amount of binder 14 is required, which reduces the active material content and the capacity. If the average molecular weight is more than 5,000,000, the viscosity of the negative electrode agent for non-aqueous electrolyte secondary batteries increases, which not only inhibits uniform dispersion of the binder 14 and particles of the electrode active material, but also makes it difficult to increase the solid content, which may deteriorate productivity. The first polymer according to the present embodiment is preferably a water-soluble polymer. The first polymer according to the present embodiment is preferably neutralized with a compound containing an alkali metal. Neutralization can improve the reactivity of the crosslinking agent described below. When a water-soluble polymer is used, the dispersibility of the silicon-based active material can be improved, and the cycle characteristics can be improved.

[0020] [Crosslinking agent] The crosslinking agent used for crosslinking the first polymer according to this embodiment can be one that reacts with a carboxyl group to form a crosslinked structure. The crosslinking agent used in this embodiment is not particularly limited as long as it is an aqueous crosslinking agent that reacts with a carboxyl group, but carbodiimide-based compounds, isocyanate-based crosslinking agents, and aziridine-based compounds that can react at room temperature in a few minutes are preferred.

[0021] The first polymer may be subjected to multiple crosslinking treatments. In addition to the above-mentioned chemical bonds using the crosslinking agent, metal ion bonds may be used for the crosslinking. For example, a multivalent cation such as a calcium ion or a magnesium ion may be used for the metal ion bond. By including a reversible crosslink such as a metal ion bond, particles of the electrode active material and the like can be uniformly dispersed in the negative electrode agent for a non-aqueous electrolyte secondary battery without being hindered by the binder 14.

[0022] The crosslinking agent according to the present embodiment has a reaction rate that depends on the pH of the aqueous polymer solution, so that dropping the crosslinking agent into an acidic polymer solution may not form a uniform crosslinked structure. Therefore, by dropping the crosslinking agent into an aqueous solution of a high molecular weight polymer that has been neutralized or esterified with a salt, the reaction proceeds slowly and a uniform crosslinked structure can be formed. Then, a low molecular weight acidic polymer is added to completely terminate the reaction, and the aqueous polymer solution can be prepared.

[0023] The amount of the crosslinking agent added is preferably such that the crosslinking functional group of the crosslinking agent is in the range of 0.5 mol% to 3.0 mol% relative to the amount of the carboxyl group of the first polymer material. If the amount of the crosslinking functional group of the crosslinking agent is less than 0.5 mol%, the crosslinked structure may be too small to obtain the effect of the present invention. If the amount of the crosslinking functional group of the crosslinking agent is more than 3.0 mol%, it is not preferable because the conductive assistant and the active material cannot be sufficiently dispersed in the negative electrode paint, i.e., the negative electrode agent for non-aqueous electrolyte secondary batteries.

[0024] [Second polymer] The second polymer according to this embodiment may contain carboxylate, and more preferably, it is a polymer having carboxylate and carboxyl groups and less active protons.The second polymer according to this embodiment may be alginic acid, carboxymethylcellulose, hyaluronic acid, rosin acid polymer, poly(meth)acrylic acid, or a polymer obtained by esterifying a copolymer of maleic acid and acrylic acid, and is particularly preferably a polyacrylic acid ester or a copolymer of polyacrylic acid ester and polyacrylic acid.

[0025] Furthermore, the content of the second polymer may be within a range of 1% by mass or more and 20% by mass or less with respect to the total mass of the polymers contained in the entire binder 14. In other words, it is preferable that the content of the second polymer in the binder 14 is less than the content of the first polymer. When the content of the second polymer is 1% by mass or more, a sufficient amount of the second polymer adheres to the active material surface. When the content of the second polymer is 20% by mass or less, a better balance is obtained between the durability of the negative electrode active material layer 10 against the internal stress caused by the volume change of the silicon-based active material 11 during charging and discharging, and the coating strength of the first polymer.

[0026] The average molecular weight of the second polymer according to this embodiment is preferably within a range of 5000 to 50,000. If the average molecular weight of the second polymer is less than 5000, the durability against the internal stress of the negative electrode active material layer 10 caused by the volume change during charging and discharging of the silicon-based active material 11 is not sufficiently obtained, and the battery performance may be deteriorated. In addition, if the average molecular weight of the second polymer is greater than 50,000, the second polymer is difficult to adsorb to the active material surface, and the battery performance may be deteriorated.

[0027] The binder 14 contained in the negative electrode agent for a nonaqueous electrolyte secondary battery according to this embodiment has a total surface area S (m 2The ratio S / B of the mass B (g) of the binder to the mass S (m) is preferably in the range of 20 to 400, and more preferably in the range of 100 to 300. If S / B is less than 20, the binder 14 becomes excessive, which may inhibit the diffusibility and conductivity of the lithium ions in the negative electrode active material layer 10 and result in a decrease in battery performance. If S / B is more than 400, the binding strength is insufficient, and sufficient coating strength cannot be obtained, which may result in a decrease in battery performance. 2 ) is the specific surface area (m 2 / g) and the mass (g) of the inorganic particles contained in the negative electrode slurry. Note that the above-mentioned "total inorganic particles" includes the electrode active material and the conductive assistant, which will be described later. The second polymer according to the present embodiment is preferably a water-soluble polymer, which can improve the dispersibility of the silicon-based active material and improve the cycle characteristics.

[0028] (electrode active material) [Silicon-based active materials] The silicon-based active material 11 is not particularly limited as long as it can reversibly absorb and release Li, and known materials can be used, but it is preferable to use a silicon material that alloys with Li. As the silicon-based active material 11, a silicon material alloyed with other elements that alloy with Li can also be used. The silicon-based active material 11 is particularly SiOx, which has a larger capacity than graphite, and more preferably, x is in the range of 0 to 1.5. If x is more than 1.5, it may not be possible to ensure a sufficient amount of Li absorption and release. In this embodiment, the silicon-based active material 11 is more preferably Si, where x is 0.

[0029] The particle size of the silicon-based active material 11 represented by SiOx is not particularly limited, but it is desirable that D50 (median diameter: diameter of particle size where the cumulative value is 50%, indicating average particle size) is in the range of 0.05 μm to 10 μm. When D50 of the silicon-based active material 11 is larger than 10 μm, the current per total active material surface area becomes large, the electrode resistance increases, and the capacity may decrease. On the other hand, when D50 is smaller than 0.05 μm, the silicon-based active material 11 is likely to aggregate in the process of preparing the negative electrode paint, and it becomes difficult to obtain a negative electrode paint in which the silicon-based active material 11 is uniformly dispersed, i.e., a negative electrode agent for non-aqueous electrolyte secondary batteries. Therefore, the electrode resistance may increase and the capacity may decrease.

[0030] [Carbon-based active materials] The carbon-based active material 12 is not particularly limited, and known materials can be used. In particular, artificial graphite and natural graphite are preferred. The particle size (D50) of the carbon-based active material 12 is not particularly limited, but is preferably 1 μm or more. If the D50 is smaller than 1 μm, the carbon-based active material 12 is likely to aggregate in the process of preparing the negative electrode paint, i.e., the negative electrode agent for non-aqueous electrolyte secondary batteries, making it difficult to obtain a negative electrode paint in which particles of the electrode active material and the like are uniformly dispersed. In addition, the increase in the specific surface area requires a large amount of binder 14, which reduces the active material content, and the capacity may decrease.

[0031] [Silicon-based active materials] The content of silicon-based active material 11 contained in the negative electrode agent for a nonaqueous electrolyte secondary battery according to this embodiment is preferably within a range of 0% by mass to 50% by mass with respect to the mass of the total active material. If the content of silicon-based active material 11 is 0% by mass, a sufficient battery capacity cannot be obtained, and if it is more than 50% by mass, the negative electrode 1 is likely to peel off from the negative electrode current collector 21 due to the effect of a volume change of silicon-based active material 11. The average particle size (D50) of the silicon-based active material 11 is preferably smaller than that of the carbon-based active material 12. For example, the average particle size of the silicon-based active material 11 is preferably in the range of 0.001 to 0.9 times the average particle size of the carbon-based active material 12, and more preferably in the range of 0.005 to 0.5 times.

[0032] (Conductive assistant) As the conductive assistant 13 contained in the negative electrode agent for non-aqueous electrolyte secondary batteries according to this embodiment, carbon black, natural graphite, artificial graphite, metal oxides such as titanium oxide and ruthenium oxide, metal fibers, etc. can be used. Among them, carbon black exhibiting a structure is preferable, and furnace black, Ketjen black, and acetylene black (AB), which are types of carbon black, are particularly preferably used. In addition, a mixture of carbon black and another conductive assistant, such as vapor grown carbon fiber (VGCF), is also preferably used. The content of the conductive assistant 13 is preferably in the range of 1% by mass or more and less than 90% by mass with respect to the mass of the total active material. If the content of the conductive assistant 13 is less than 1% by mass, the conductivity may be insufficient and the electrode resistance may increase, whereas if it is 90% by mass or more, the amount of active material may be insufficient and the lithium absorption capacity may decrease.

[0033] <Negative electrode for non-aqueous electrolyte secondary battery and method for producing same> (Negative electrode active material layer) The negative electrode active material layer 10 according to this embodiment can be formed by applying and drying a slurry-like negative electrode agent for non-aqueous electrolyte secondary batteries to which a solvent has been added, in addition to the above-mentioned mixture of the silicon-based active material 11, the carbon-based active material 12, the conductive assistant 13, and the mixed binder 14 containing a first polymer partially crosslinked and a second polymer containing a carboxylate, onto a current collector 21. The solvent contained in the negative electrode agent for non-aqueous electrolyte secondary batteries is not particularly limited as long as it can dissolve the resin contained in the binder 14, and examples of the solvent include organic solvents such as N-methylpyrrolidone and N,N-dimethylformamide, and water.

[0034] (current collector) For the current collector 21, any material conventionally used as a negative electrode current collector material for secondary batteries may be appropriately used. Examples include aluminum, nickel, copper, iron, stainless steel (SUS), titanium, etc. In particular, copper is particularly preferable from the viewpoints of electronic conductivity and battery operating potential. The general thickness of such a current collector 21 is about 10 to 30 μm. 2 is a schematic cross-sectional view showing the configuration of a known coin cell 20 used to evaluate energy density. Inside the coin cell 20, a negative electrode 1 and a positive electrode 23 face each other with a separator 22 between them, and a sufficient amount of electrolyte 24 is filled around them. The exterior of the coin cell 20 is arranged with a negative electrode case 25 on the negative electrode side and a positive electrode case 26 on the positive electrode side, and a gasket 27 is provided on the circumferential part (outer periphery) of the positive electrode case 26.

[0035] The positive electrode 23 may have a laminated structure in which a Li metal foil or a positive electrode active material layer and a positive electrode current collector (not shown) are laminated. The positive electrode active material constituting the positive electrode active material layer may be any material capable of absorbing and releasing lithium, and may be any known positive electrode active material for non-aqueous electrolyte secondary batteries. Specifically, the positive electrode active material may be, for example, lithium manganese oxide, lithium nickel oxide, lithium cobalt oxide, lithium iron oxide, lithium nickel manganese oxide, lithium nickel cobalt oxide, lithium nickel manganese cobalt oxide, or a lithium transition metal phosphate compound. Note that a mixture of a plurality of the above active materials may be used as the positive electrode active material.

[0036] The positive electrode active material layer may contain a conductive assistant and a binder in addition to the positive electrode active material. As the conductive assistant contained in the positive electrode active material layer, for example, known materials such as acetylene black, ketjen black, carbon black, graphite, and carbon nanotubes can be used. The binder contained in the positive electrode active material layer is not particularly limited as long as it can adhere the mixture of the positive electrode active material and the conductive assistant to the current collector. Examples of such binders include polyvinylidene fluoride and polytetrafluoroethylene.

[0037] For the current collector (not shown) in the positive electrode 23, a material conventionally used as a positive electrode current collector material for secondary batteries may be appropriately adopted. Examples include aluminum, nickel, copper, iron, stainless steel (SUS), titanium, etc. In particular, aluminum is particularly preferable from the viewpoint of electronic conductivity and battery operating potential. The general thickness of such a current collector is about 10 to 30 μm. The separator 22 is disposed between the positive electrode 23 and the negative electrode 1, which are disposed opposite to each other. As a result, the separator 22 electrically insulates the positive electrode 23 from the negative electrode 1. As the separator 22, for example, a microporous membrane made of polyolefin such as polyethylene or polypropylene, a microporous membrane made of aromatic polyamide resin, a nonwoven fabric, a porous resin coat containing inorganic ceramic powder, or the like can be used.

[0038] The electrolytic solution 24 is filled in a space defined by the negative electrode case 25, the positive electrode case 26, and the gasket 27. The electrolytic solution 24 is composed of a solvent and an electrolyte. Examples of the solvent of the electrolyte solution 24 used in the nonaqueous electrolyte secondary battery according to this embodiment include low-viscosity chain carbonates such as dimethyl carbonate and diethyl carbonate, high-dielectric-constant cyclic carbonates such as ethylene carbonate, propylene carbonate and butylene carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, methyl acetate, methylpropionate, vinylene carbonate, dimethylformamide, sulfolane, and mixed solvents thereof.

[0039] The electrolyte contained in the electrolytic solution 24 is not particularly limited, and examples thereof include LiClO4, LiBF4, LiAsF6, LiPF6, LiCF3SO3, LiN(CF3SO2)2, LiI, LiAlCl4, and mixtures thereof. A lithium salt of one or a mixture of two or more of LiBF4 and LiPF6 is preferable. The gasket 27 is a member for preventing short circuits between terminals and leakage of the electrolyte. As the gasket 27, a known gasket can be used.

[0040] The negative electrode for a non-aqueous electrolyte secondary battery according to the present embodiment and the method for producing the same will be described below with reference to specific examples and comparative examples. Note that the present invention is not limited to the following examples. Example 1 11.4 g of alginic acid (Wako Pure Chemical Industries, average molecular weight 500,000) and 6.33 g of sodium hydroxide (Kanto Chemical) were added to 271 g of water and stirred with a disperser. Next, 11.5 g of a 1% aqueous solution of calcium chloride was added to this polymer solution and stirred for 20 minutes. As a result, a 5% aqueous solution of the first polymer was prepared.

[0041] 84g of water was added to 13.1g of the obtained aqueous solution of the first polymer and stirred. Next, 8.2g of Si particles (average particle size 2μm) as a silicon (Si)-based active material, 24.6g of artificial graphite (Gr) as a carbon (C)-based active material, 3.28g of acetylene black (AB) and 3.28g of vapor-grown carbon fiber (VGCF) as a conductive assistant, and 0.16g of a copolymer of acrylic acid ethyl ester and maleic acid (average molecular weight 30,000, monomer blending molar ratio 50:50) as a second polymer were added, and stirred with a disper equipped with a disk turbine blade as a stirring blade. Then, the mixture was dispersed using Filmix (manufactured by Primix Corporation) to obtain a negative electrode slurry (negative electrode agent for non-aqueous electrolyte secondary batteries) of Example 1. In the negative electrode slurry of Example 1, the total surface area of ​​all inorganic particles S (m 2 The ratio S / B of the mass B (g) of the binder to the mass S (g) of the second polymer was 410, and the content ratio (%) of the second polymer to the total mass of the polymers contained in the entire binder was 25.

[0042] Example 2 A negative electrode slurry of Example 2 was obtained in the same manner as in Example 1, except that the average molecular weight of the first polymer was set to 5,000,000. Example 3 A negative electrode slurry of Example 3 was obtained in the same manner as in Example 1, except that the first polymer was hyaluronic acid. Example 4 A negative electrode slurry of Example 4 was obtained in the same manner as in Example 1, except that the first polymer was a salt of a copolymer of maleic acid and acrylic acid. Example 5 A negative electrode slurry of Example 5 was obtained in the same manner as in Example 1, except that the first polymer was a carboxymethyl cellulose salt.

[0043] Example 6 A negative electrode slurry of Example 6 was obtained in the same manner as in Example 1, except that the first polymer was a polyacrylate and the second polymer was a copolymer of ethyl acrylate and acrylic acid. Example 7 A negative electrode slurry of Example 7 was obtained in the same manner as in Example 2, except that the first polymer was a polyacrylate and the second polymer was a copolymer of ethyl acrylate and acrylic acid. Example 8 The sum of the surface areas of all inorganic particles S(m 2 A negative electrode slurry of Example 8 was obtained in the same manner as in Example 1, except that the negative electrode composition ratio was changed so that the ratio S / B of the mass of the binder (g) to the mass of the binder (B) was 21. Example 9 The sum of the surface areas of all inorganic particles S(m 2 A negative electrode slurry of Example 9 was obtained in the same manner as in Example 2, except that the negative electrode composition ratio was changed so that the ratio S / B of the mass of the binder (g) to the mass of the binder (B) was 328.

[0044] Example 10 A negative electrode slurry of Example 10 was obtained in the same manner as in Example 1, except that the type of the crosslinking agent was a carbodiimide-based crosslinking agent. Example 11 A negative electrode slurry of Example 11 was obtained in the same manner as in Example 1, except that the type of the crosslinking agent was an isocyanate-based crosslinking agent. Example 12 A negative electrode slurry of Example 12 was obtained in the same manner as in Example 1, except that the type of the crosslinking agent was an aziridine-based compound. Example 13 A negative electrode slurry of Example 13 was obtained in the same manner as in Example 1 except that the content ratio (%) of the second polymer to the total mass of the polymers contained in the entire binder was set to 1. Example 14 A negative electrode slurry of Example 14 was obtained in the same manner as in Example 2, except that the content ratio (%) of the second polymer to the total mass of the polymers contained in the entire binder was set to 20.

[0045] Example 15 The first polymer is a polyacrylate salt, its average molecular weight is 1 million, the type of crosslinking agent is an aziridine compound, the second polymer is a copolymer of acrylic acid ethyl ester and acrylic acid, its average molecular weight is 30,000, and the sum of the surface areas of all inorganic particles S(m 2 The negative electrode slurry of Example 15 was obtained in the same manner as in Example 1, except that the ratio S / B of the mass B (g) of the second polymer to the mass of the binder was set to 164, and the content ratio (%) of the second polymer to the total mass of the polymers contained in the entire binder was set to 10. (Example 16) A negative electrode slurry of Example 16 was obtained in the same manner as in Example 15, except that the average molecular weight of the first polymer was 5,000,000. (Example 17) A negative electrode slurry of Example 17 was obtained in the same manner as in Example 15, except that the average molecular weight of the second polymer was 5,000. (Example 18) The sum of the surface areas of all inorganic particles S(m 2 The negative electrode slurry of Example 18 was obtained in the same manner as in Example 15, except that the ratio S / B of the mass of the binder (g) to the mass B (g) of the binder was set to 27.

[0046] Comparative Example 1 A negative electrode slurry of Comparative Example 1 was obtained in the same manner as in Example 15, except that the molecular weight of the first polymer was 490,000. Comparative Example 2 A negative electrode slurry of Comparative Example 2 was obtained in the same manner as in Example 15, except that the molecular weight of the first polymer was set to 5.1 million. Comparative Example 3 A negative electrode slurry of Comparative Example 3 was obtained in the same manner as in Example 15, except that the molecular weight of the second polymer was 4,000. Comparative Example 4 A negative electrode slurry of Comparative Example 4 was obtained in the same manner as in Example 15, except that the molecular weight of the second polymer was 51,000. Comparative Example 5 A negative electrode slurry of Comparative Example 5 was obtained in the same manner as in Example 15, except that no crosslinking agent was added.

[0047] The negative electrode slurries obtained in Examples 1 to 18 and Comparative Examples 1 to 5 were applied to a current collector. A copper foil having a thickness of 12 μm was used as the current collector. The negative electrode slurry was applied at a concentration of 1.0 mg / cm 2 The coating was applied with a doctor blade so that the coating weight was 1.0 g / cm. Then, the coating was pre-dried at 80°C for 30 minutes. 3 The negative electrode was obtained by drying under reduced pressure at 105° C. for 5 hours.

[0048] (Cell Preparation) The obtained negative electrode and a 300 μm thick Li metal foil positive electrode were sandwiched between a negative electrode case and a positive electrode case with a separator (model number 2200, manufactured by Celgard) between them to prepare a coin cell. The positive electrode was punched out into a disk with a diameter of 15 mm, and the Li metal foil was punched out into a disk with a diameter of 16 mm for evaluation. The electrolyte used was a mixture of ethylene carbonate (EC) and diethyl carbonate (DMC) at a ratio of 3:7 (by volume), to which LiPF6 was added to make a 1M solution, and further 10% by mass of fluoroethylene carbonate (FEC) and 1% by mass of vinylene carbonate (VC) were added.

[0049] (evaluation) <Discharge capacity> The discharge capacity was determined as follows. Charge and discharge were performed at 0.01 V to 1.5 V. First, constant current charge and discharge at 0.05 C was performed three times to evaluate the initial discharge capacity, and then a cycle test of constant current charge at 0.5 C and constant current discharge at 0.5 C was performed for 100 cycles. In this example, the discharge capacity was evaluated according to the following criteria. ⊚: The discharge capacity at the 100th cycle is extremely good compared to the discharge capacity at the 1st cycle. ◯: The discharge capacity at the 100th cycle is better than the discharge capacity at the 1st cycle. △: The discharge capacity at the 100th cycle is slightly better than that at the 1st cycle. ×: The discharge capacity at the 100th cycle is inferior to the discharge capacity at the 1st cycle. In this embodiment, "◎", "◯", and "Δ" were deemed to be at a level that did not pose a problem in use and were therefore rated as "pass".

[0050] <Coating properties of negative electrode slurry> The coatability of the negative electrode slurry was determined as follows. The negative electrode slurries obtained in Examples 1 to 18 and Comparative Examples 1 to 5 were applied to the current collector at a concentration of 1.0 mg / cm 2 The coating was applied with a doctor blade to a coating weight of 100g. In this example, the coating properties of the negative electrode slurry were evaluated according to the following criteria. ⊚: The coating layer has extremely high uniformity. ◯: The coating layer has uniformity, although it is inferior to ⊚. △: Inferior to ◯, but the coating layer has uniformity that does not cause any practical problems. ×: The coating layer clearly lacks uniformity. In this embodiment, "◎", "◯", and "Δ" were deemed to be at a level that did not pose a problem in use and were therefore rated as "pass". The results of each evaluation are shown in Table 1 below.

[0051] [Table 1]

[0052] It was found that Examples 1 to 18 had a higher discharge capacity at the 100th cycle than Comparative Examples 1 to 5. In Comparative Example 1, the molecular weight of the first polymer was small, and sufficient binding properties of the active material layer were not obtained, resulting in a low discharge capacity. In Comparative Example 3, the molecular weight of the second polymer was small, and the binder could not follow the volume change of Si, resulting in a low discharge capacity. In Comparative Example 5, the first polymer was not crosslinked, and therefore sufficient binding properties of the active material layer were not obtained, and furthermore, the binder could not follow the volume change of Si, resulting in a low discharge capacity. In Comparative Example 2, the molecular weight of the first polymer was too large and thickened, resulting in a poor application property of the negative electrode slurry, and a negative electrode could not be produced. In Comparative Example 4, the molecular weight of the second polymer was large, and therefore it was difficult to adsorb to the surface of the active material, resulting in a low discharge capacity.

[0053] From the above, the effects of the present invention were confirmed. The scope of the present invention is not limited to the exemplary embodiments shown and described, but includes all embodiments that achieve equivalent effects to the object of the present invention. Moreover, the scope of the present invention is not limited to the combination of inventive features defined by the claims, but may be defined by any desired combination of specific features among all the respective disclosed features. [Explanation of symbols]

[0054] 1 negative electrode 10 Negative electrode active material layer 11 Silicon-based active materials 12 Carbon-based active materials 13 Conductive additives 14. Binder 20 coin cell 21 Negative electrode current collector 22 Separator 23 Positive electrode 24 Electrolyte 25 Negative electrode case 26 Positive electrode case 27 Gasket

Claims

1. A negative electrode agent for a non-aqueous electrolyte secondary battery, comprising an electrode active material, a conductive assistant, and a binder, the binder is a mixed binder including a first polymer having an average molecular weight in the range of 500,000 to 5,000,000 and a second polymer having an average molecular weight in the range of 5,000 to 50,000, The electrode active material includes a silicon-based active material and a carbon-based active material, the first polymer has an ethylenically unsaturated carboxylate and a crosslinked structure, the second polymer is a copolymer of an ethylenically unsaturated carboxylic acid compound and an ethylenically unsaturated compound containing an alkyl carboxylate group, 1. A negative electrode agent for a non-aqueous electrolyte secondary battery, comprising: a negative electrode agent having a ratio S / B of a sum S (m 2 ) of surface areas of all inorganic particles in the negative electrode agent to a mass B (g) of the binder, the ratio being within a range of 20 to 400.

2. A negative electrode agent for a non-aqueous electrolyte secondary battery, comprising an electrode active material, a conductive assistant, and a binder, the binder is a mixed binder including a first polymer having an average molecular weight in the range of 500,000 to 5,000,000 and a second polymer having an average molecular weight in the range of 5,000 to 50,000, The electrode active material includes a silicon-based active material and a carbon-based active material, the first polymer has an ethylenically unsaturated carboxylate and a crosslinked structure, the second polymer is a copolymer of an ethylenically unsaturated carboxylic acid compound and an ethylenically unsaturated compound containing an alkyl carboxylate group, a content ratio of the second polymer in the mixed binder of 1% by mass or more and 20% by mass or less based on the total mass of the polymers contained in the mixed binder;

3. The first polymer is a cross-linked polymer of a polyacrylate having an average molecular weight in the range of 500,000 to 5,000,000, 3. The negative electrode agent for a non-aqueous electrolyte secondary battery according to claim 1, wherein the second polymer is a copolymer of polyacrylic acid ester and polyacrylic acid having an average molecular weight in the range of 5,000 to 50,000.

4. 4. The negative electrode agent for a non-aqueous electrolyte secondary battery according to claim 1, wherein the first polymer is crosslinked with any one of a carbodiimide-based compound, an isocyanate-based crosslinking agent, and an aziridine-based compound.

5. 5. The negative electrode agent for a non-aqueous electrolyte secondary battery according to claim 1, wherein the first polymer is crosslinked with an aziridine compound.

6. A negative electrode for a non-aqueous electrolyte secondary battery, formed by using the negative electrode agent according to any one of claims 1 to 5.

7. A non-aqueous electrolyte secondary battery comprising a negative electrode for a non-aqueous electrolyte secondary battery formed using the negative electrode agent according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Anode active material, and lithium cell which adopted this

    JP2007157709A

  • Electrode mixture coating material for nonaqueous electrolyte secondary battery, electrode for nonaqueous electrolyte secondary battery, method of manufacturing electrode for nonaqueous electrolyte secondary battery, and nonaqueous electrolyte secondary battery

    JP2015056269A

  • Electrode for nonaqueous electrolyte secondary battery

    JP2016219370A

  • Negative electrode for lithium ion secondary battery and lithium ion secondary battery including the same

    JP2017152121A

  • Negative electrode binder for nonaqueous electrolyte secondary battery, and negative electrode for nonaqueous electrolyte secondary battery

    JP2018147826A